KECEMASAN MEMPEROLEH PASANGAN HIDUP PADA PENYANDANG CACAT TUBUH - Rifayani, Hastuti (TALENTA, 2012)
Each periode of development has the development task that must be mastered, if the individual is not able to master one task will lead to the development of crisis raises anxiety. One of the development task of early adulthood in choosing a  life partner. The aimed of this study is to understanding how people with disabilities in getting a life partner, what symptoms of anxiety experienced by, any factors affected and how strategic coping been used. Subject of this study consist of 3 persons who have the characteristics of persons with disabilities, men and women. Age 20-30, Surakarta research sites. Observation, depth interview and documentation are used as data methods and descriptive analysis used as data analysis.   The data analysis show that disabilities persons get anxiety from families denial and denial of environment partners, increasing age, do not yet have a sing of the couples, worried for his or her partner a bandoned, has no descendants, anxious not to get a better pair of physical condition from his or her.   The physical symptom are : anger, insomnia, no appetite, heart beats, shocked, the body chills, headache, fever, less focus, moody, sensitive, less enthusiastic, lazy, less attraction and fear.   The factors influencing anxiety  in getting couples to physical trauma defect, condition and the environment, how to evercome problems through escapism, minimization, self blame, seeking meaning and instrumental action.